Edukasi Upaya Deteksi Dini Kanker Serviks di Wilayah Kerja Puskesmas Tahtul Yaman Kota Jambi - M.Dody Izhar; Marta Butar Butar; Willia Novita Eka Rini (Jurnal Salam Sehat Masyarakat (JSSM), 2021)
Community preparation in carrying out early detection of cervical cancer such as VIA examination in the form of community mobilization (Empowerment) is needed so that awareness, knowledge and ability of IVA examination targets in carrying out VIA examinations increase according to the Ministry of Health in 2015. With this improvement, it is expected to increase the coverage of VIA examinations at the puskesmas, especially in this case at the Tahtul Yaman Health Center. Community service is carried out through socialization in the form of counseling on early detection of cervical cancer and educational training activities for cervical cancer early detection. The results of the socialization of cervical cancer early detection and training on cervical cancer early detection education showed that there was an increase in the knowledge of participants who took part in the activity compared to before and after participating in the training, from 78.33 to 85.56. Statistical results obtained p value = 0.002, meaning that there is a significant difference in the average test scores before being given training and after being given training. It is hoped that there will be the formation of Educational Cadres for Early Detection of Cervical Cancer in the Work Area of the Tahtul Yaman Health Center in Jambi City and the provision of pocket books that are easily understood by the public.